Rheological characteristics of unaged and aged epoxidised natural rubber modified asphalt - Al-Mansob, R.A.; Ismail, A.; Yusoff, N.I.M.; Albrka, S.I.; Azhari, C.H.; Karim, M.R. (Elsevier, 2016)
Durable pavement with long service life and low maintenance and rehabilitation costs are preferred; hence, the demand for high-quality asphalt is growing. This situation has led to the research and development of new materials with increased performance, such as polymer-modified asphalt (PMA). This study was conducted to investigate the use of epoxidised natural rubber (ENR) mixed with asphalt, both unaged and aged. The physical and rheological properties of base asphalt and ENR-modified asphalt (ENRMAs) were measured. Fundamental parameters were used to describe the significant benefits of ENR as a modifier. However, it was observed that the rheological properties differ considerably between the base asphalt and ENRMAs. The rheological parameters of complex modulus and phase angle indicate that the presence of ENR increases the stiffness and elasticity behaviour of the binder, particularly at high temperatures. For the aged binders, the dynamic mechanical analysis of the effect of ageing on the rheological performance of the binders indicated that there is a considerable difference in behaviour between the base asphalt and PMAs. Based on the dynamic mechanical analysis of the binders, it can be concluded that the asphalt component of the modified binders ages in a manner similar to that of the base asphalt. However, the rheological changes that occur after ageing differ from the base asphalt in regions where the polymer is the dominant component. Finally based on the physical and rheological tests, it can be concluded that ENR can increase the durability of asphalt pavements.